1987
DOI: 10.1063/1.98999
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gaseous oxygen using diode laser spectroscopy

Abstract: A commercial diode laser emitting at ∼761 nm has been used to detect the absorption of individual rotational lines of the A band of atmospheric oxygen. An output signal that is proportional to the O2 partial pressure is extracted using derivative spectroscopy. The method allows measurement of O2 pressure with an uncertainty of ±1.3% of full scale (760 Torr) using a 1-ms time constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Since transitions in the A band near 760 nm are spin forbidden, direct absorption measurements of O 2 is complicated due to the very weak absorption cross sections [29]. One method for overcoming this limitation is the use of a derivative technique of spectroscopy with second harmonic (2f) detection as demonstrated by Kroll et al [30], Philippe and Hanson [29], and Rieker and Hanson [31]. The 2f technique utilizes a high frequency modulation of the output wavelength of a laser diode as its wavelength is scanned across the absorption line.…”
Section: Introductionmentioning
confidence: 99%
“…Since transitions in the A band near 760 nm are spin forbidden, direct absorption measurements of O 2 is complicated due to the very weak absorption cross sections [29]. One method for overcoming this limitation is the use of a derivative technique of spectroscopy with second harmonic (2f) detection as demonstrated by Kroll et al [30], Philippe and Hanson [29], and Rieker and Hanson [31]. The 2f technique utilizes a high frequency modulation of the output wavelength of a laser diode as its wavelength is scanned across the absorption line.…”
Section: Introductionmentioning
confidence: 99%
“…Die kostengünstigen, einmodig und vor allem bei Raumtemperatur arbeitenden NIR-DL wurden aber auch in der Gasanalytik eingesetzt [3][4][5], wobei Sauerstoff eines der ersten Moleküle war, das in Laborversuchen quantitativ mit NIR-DL nachgewiesen wurde [6]. Inzwischen stehen durch die ra- …”
Section: Nir-diodenlaser Für Den Gasnachweisunclassified
“…Due to its atmospheric abundance and fairly simple, well-known spectroscopy, molecular oxygen has been a popular measurement species for diode laser experiments. Early measurements of oxygen absorption near 761 nm showed that accurate concentration values could be determined within 1% accuracy at 1 kHz (Kroll et al 1987) using traditional distributed feedback (DFB) lasers. The typical DFB lasers in this spectral region were limited in terms of wavelength tuning capability, and thus could not offer simple, high-resolution measurements of temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%